The Impact of Dynamic Capabilities and Information System on Organizational Effectiveness in Cellular Communication Companies in Jordon: Mediating Role of Organizational Ambidexterity - Atif Aziz; Ramsha Zaki; Syed Ehsan Ullah (International Journal of Informatics and Information Systems, 2020)
The goal of the ongoing research is to examine the impact of dynamic capabilities such as exploitation capability, exploration capability and information system on the organizational effectiveness of cellular communication firms in Jordan. The examination of the mediating role of organizational ambidexterity among the nexus of dynamic capabilities such as exploitation capability and exploration capability and organizational effectiveness is also included in the goals of the ongoing research. The quantitative method of data gathering has been utilized by the researchers to collect the data from the employees of the cellular communication firms currently operating in Jordan while AMOS has been used for the purpose of analysis. The results exposed that the positive nexus has been found among the nexus of dynamic capabilities, organizational ambidexterity, and organizational effectiveness. The results also revealed that the organizational ambidexterity has positive mediating among the links of dynamic capabilities such as exploitation capability and exploration capability on organizational effectiveness. These findings are suitable for the regulation developing authorities that they should develop and implement the effective regulation related to the dynamic capabilities and organizational ambidexterity that enhance the organizational effectiveness of the firm.